Risk of hydrogen sulfide pollution from pressure release resulting from landfill mining - Zhou, Haomin; Jia, Jia; Tang, Lu; Shen, Dongsheng; Hu, Lifang; Long, Yuyang (Journal of hazardous materials, 2024)
Landfill mining (LFM) has gained widespread recognition due to its benefits in terms of resource utilization of landfill waste and reuse of landfill sites. However, it is important to thoroughly assess the associated environmental risks. This study simulated the pressure release induced from LFM in small-scale batch anaerobic reactors subject to different initial pressures (0.2–0.6 MPa). The potential risk of hydrogen sulfide (H2S) pollution resulting from pressure release caused by LFM was investigated. The results demonstrated that the concentration of H2S significantly increased following the simulated pressure treatments. At the low (25 °C) and high (50 °C) temperatures tested, the peak H2S concentration reached 19366 and 24794 mg·m−3, respectively. Both of these concentrations were observed under highest initial pressure condition (0.6 MPa). However, the duration of H2S release was remarkably longer (>90 days) at the low temperature tested. Microbial diversity analysis results revealed that, at tested low temperature, the sulfate-reducing bacteria (SRB) communities of various pressure-bearing environments became phylogenetically similar following the pressure releases. In contrast, at the high temperature tested, specific SRB genera (Desulfitibacter and Candidatus Desulforudis) showed further enrichment. Moreover, the intensified sulfate reduction activity following pressure release was attributed to the enrichment of specific SRBs, including Desulfovibrio (ASV585 and ASV1417), Desulfofarcimen (ASV343), Candidatus Desulforudis (ASV24), and Desulfohalotomaculum (ASV506 and ASV2530). These results indicate that the pressure release associated with LFM significantly increases the amount of H2S released from landfills, and the SRB communities have different response mechanisms to pressure release at different temperature conditions. This study highlights the importance of considering the potential secondary environmental risks associated with LFM. [Display omitted] •Pressure release associated with LFM increased peak H2S concentration 7-12 times.•The pressure release of 0.6 MPa leaded to most serious H2S pollution risk.•Microbial communities became phylogenetically similar following pressure release.•Desulfovibrio was the main functional SRB following pressure release at 25 ℃.•Functional SRB demonstrated greater diversity following pressure release at 50 °C.